2019
DOI: 10.1111/irv.12658
|View full text |Cite
|
Sign up to set email alerts
|

Associations between common respiratory viruses and invasive group A streptococcal infection: A time‐series analysis

Abstract: Background Invasive infections by group A S treptococcus (iGAS, Streptococcus pyogenes ) have a winter seasonality which largely coincides with the season for influenza and other respiratory viruses. Influenza superinfections with GAS have been described to occur regularly and to show a severe clinical picture with high mortality. We aimed to study the extent to which influenza A and B viruses (IAV and IBV), respiratory syncytial virus (RSV) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 19 publications
(29 reference statements)
2
25
0
Order By: Relevance
“…We observed 10 different emm types among STSS cases that had an isolate submitted for typing, indicating a lack of clonality. Of note, a study in the Netherlands identified a temporal association between STSS and influenza A virus ( 27 ). However, STSS cases in Idaho occurred throughout the year, without seasonal patterns that might have been associated with influenza.…”
Section: Discussionmentioning
confidence: 99%
“…We observed 10 different emm types among STSS cases that had an isolate submitted for typing, indicating a lack of clonality. Of note, a study in the Netherlands identified a temporal association between STSS and influenza A virus ( 27 ). However, STSS cases in Idaho occurred throughout the year, without seasonal patterns that might have been associated with influenza.…”
Section: Discussionmentioning
confidence: 99%
“…pyogenes disease, their role in modulating the host-pathogen interaction is complex and poorly understood, particularly in relation to colonization of the pharynx [8,9,[18][19][20][21]. As respiratory viruses frequently infect the colonizing sites of bacteria, it is important to understand their impact on potentially pathogenic bacteria such as S. pyogenes.…”
Section: Discussionmentioning
confidence: 99%
“…93 Clinically, S. pyogenes infections secondary to influenza are often accompanied by pneumonia, septicemia, and necrotizing fasciitis. 7,[94][95][96] Microbiological studies of lung tissue and blood culture samples from the Spanish influenza pandemic suggested that S. pyogenes as well as S. pneumoniae and S. aureus were the most common related pathogens, and responsible for the majority of lethal courses. 4,31 Furthermore, a time-series analysis of case reports revealed an ecological temporal association (up to 40%) between IAV and toxic shock syndrome, a severe complication of S. pyogenes infection.…”
Section: Co-infection With S Pyogenesmentioning
confidence: 99%
“…4,31 Furthermore, a time-series analysis of case reports revealed an ecological temporal association (up to 40%) between IAV and toxic shock syndrome, a severe complication of S. pyogenes infection. 94…”
Section: Co-infection With S Pyogenesmentioning
confidence: 99%
See 1 more Smart Citation